A novel autonomous remote system applied in agriculture using transmission control protocol - Anass Deroussi; Abdessalam Ait Madi; Imam Alihamidi; Lalla Amina Charaf; Mohammed Saber; Anass Erraoui; Adnane Addaim (Institute of Advanced Engineering and Science, 2022)
An internet of things (IoT) irrigation system is challenged by several issues, such as cost, energy consumption, and data storage. This paper proposes a novel energy-efficient, cost-effective IoT system called